Monetary-Policy Rule as a Bridge: Predicting Inflation without Predictive Regressions - Hua, Jian; Wu, Liuren (Journal of Financial and Quantitative Analysis, 2018)
A major issue with predicting inflation rates using predictive regressions is that estimation errors can overwhelm the information content. This article proposes a new approach that uses a monetary-policy rule as a bridge between inflation rates and short-term interest rates and relies on the forward-interest-rate curve to predict future interest-rate movements. The 2-step procedure estimates the predictive relation not through a predictive regression but far more accurately through the contemporaneous monetary-policy linkage. Historical analysis shows that the approach outperforms random walk out of sample by 30%–50% over horizons from 1 to 5 years.